INFIDELITY-THEMED MOVIES VIEWED THROUGH THE LENS OF POPULAR CULTURE - Sriastuti, Anna (Rubikon : Journal of Transnational American Studies, 2026)
In the middle of the rapid digital current, human relations are getting weaker. One of the concerns pertaining to the relationship is infidelity. It has emerged as a significant issue across various cultures, including that of Indonesia, in which infidelity has become a daily consumption topic.  It is not just seen as a real scene, but also in literary works as literary works usually mirrors what happens in a society. Popular films, like “Supernova: Ksatria, Putri, & Bintang Jatuh”, “Surga Yang Tak Dirindukan”, “Layangan Putus” and “Ipar Adalah Maut” are some popular Indonesian films on infidelity. The popularity can be seen from the film ratings of IMDb. It arises a quest why the movie theme of infidelity becomes popular in Indonesia. This dilemma is based on Indonesia values and morals perceive infidelity as a taboo subject/issue Using a qualitative method through questions, participant context data, inductive analysis, and researcher interpretations, the popularity of infidelity through Indonesian movies is seen through the application of the elements of the house of popular culture introduced by Nachbar and Lause (1992). In the analysis it is found that although Indonesia values and laws forbid infidelity, but the fact tells that infidelity still occurs. The popularity of the films is also supported by the celebrities who become the magnets of the films. So real the actors and actresses play the roles that viewers can relate the stories with the stories in real lives.